Renoprotective Activity of pioglitazone on Ischemia/Reperfusion Induced Renal Damage in diabetic Rats - Nehal Shah, Jagdish Kakadiyaï€ª, Jigar Brambhatt (Recent Research in Science and Technology, 2010)
Present study was designed to evaluate in Renoprotective activity of Pioglitazone on Ischemia/reperfusion (I/R) induced renal damage in diabetic rats. Ischemia/reperfusion injury, which is commonly seen in the field of renal surgery or transplantation in diabetic condition, is a major cause of acute renal failure. Type 2 Diabetes was induced in rats by a single intraperitoneal (i.p) injection of Streptozotocin (65 mg/kg, STZ) in overnight fasting rats followed by the i.p administration of Nicotinamide (110 mg/kg, NIC) after 15 minutes. After right nephrectomy, Piogltazone (10 mg/kg/day, p.o) was administered for 15 days. On the 16th day, ischemia was induced in contra lateral kidney for 45 min, followed by reperfusion for 24 hr. Renal function marker and oxidative parameter were estimated at the end of 24 hr reperfusion.Ã‚Â  At the end of experimental period the level of malondialdehyde formation/ lipid peroxidation (LPO) in kidney tissue and serum marker Creatinine, Urea and Uric acids were significantly increased. Whereas, the activity of biomarkers of oxidative stress such as reduced glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) were found to be decreased significantly compared to control rats. Pioglitazone improved the renal dysfunction and oxidative stress after renal ischemia/reperfusion injury in diabetic rats. In conclusion, Pioglitazone shows potent may improve renal function marker and oxidative stress in kidney in I/R induced renal damage in type 2 diabetic rats.